"Regulatory capture" and "extractive hegemony": the relevance of Nicos Poulantzas' theory of the state to contemporary environmental politics in Canada. Issue 2 (July 2020) - Bernauer, Warren
This paper considers the relevance of Nicos Poulantzas' theory of the state to debates about hydrocarbon extraction and environmental assessment in Canada. I begin with a brief summary of Poulanztas' work, followed by an overview of the politics of hydrocarbon extraction in Canada. Next, I examine recent public policy debates about the assessment and regulation of energy extraction in Canada. These debates, which focus on the concept of "regulatory capture, " fall victim to many of the problems Poulantzas identifies with instrumentalist approaches to the state. Critical accounts of regulatory capture have helped expose the fact that oil companies exercise an incredible degree of control over the Canadian state. However, it offers limited guidance for long-term strategies to confront extractive capital. In the section on "Environmental assessment and extractive hegemony, " I draw on Poulantzas to examine recent academic debates about the role of environmental assessment in the reproduction of extractive capitalism in Canada. Scholars have shown a more nuanced understanding of the power dynamics at play in the assessment and regulation of energy projects in Canada. Nevertheless, engagement with Poulantzas' work can help deepen and expand these critiques, especially his emphasis on the role of state-organized material concessions in producing consent to capitalism.